Cytokines released from blood monocytes and expressed in mucocutaneous lesions of patients with paracoccidioidomycosis evaluated before and during trimethoprim-sulfamethoxazole treatment - Parise-Fortes, M. R.; Marques, Silvio Alencar [UNESP]; Soares, AMVC; Kurokawa, Cilmery Suemi [UNESP]; Marques, MEA; Peracoli, MTS (Blackwell Publishing, 2006)
Background Mucocutaneous lesions in paracoccidioidomycosis are granulomatous and result from tissue responses to Paracoccidioides brasiliensis, the aetiological agent.Objectives and methods In this study we investigate the expression of tumour necrosis factor (TNF)-alpha, interleukin (IL)-10 and transforming growth factor (TGF)-beta 1 by immunohistochemistry in skin and mucosa lesions from patients with the chronic form of paracoccidioidomycosis, evaluated before and at day 20 of trimethoprim-sulfamethoxazole treatment. Cytokine production by peripheral blood monocytes was also studied by enzyme immunoassay.Results Intense immunostaining for TNF-alpha was detected in mononuclear cells that infiltrated granulomas in all skin and mucosa lesions before treatment simultaneously with low IL-10 granular deposits in these cells. At day 20 of treatment, there was reduced TNF-alpha and IL-10 deposition. Immunoreactive TGF-beta 1 was observed diffusely in the dermis and generally in the cytoplasm of macrophages and giant cells, before treatment, and as increased TGF-beta 1 deposits in the fibrosis area at day 20 of treatment. Peripheral blood monocytes from patients with paracoccidioidomycosis, evaluated before treatment, produced high endogenous levels of TNF-alpha, TGF-beta 1 and IL-10 in relation to healthy controls. Lipopolysaccharide-stimulated monocytes from patients secreted lower levels of TNF-alpha in both periods of evaluation while no impairment in capacity of IL-10 and TGF-beta production was observed.Conclusions Trimethoprim-sulfamethoxazole therapy was effective in decreasing fungal load in the lesions, allowing patient immune response to control the infection leading to the healing of the lesions.
Keywords: cytokines; enzyme-linked immunosorbent assay; immunohistochemistry; monocytes; paracoccidioidomycosis